Conversational-Linguistic Politeness for Chatbot Design: an Evaluation of Parameters and Card-Based Approaches - Monteiro, Mateus de Souza; Pereira, Vinícius Carvalho; Salgado, Luciana Cardoso de Castro (Journal on Interactive Systems, 2026)
Chatbots often find it challenging to meet user expectations by providing appropriate responses and engaging in natural dialogues. Previous research suggests that incorporating linguistic and conversational strategies, particularly those centered on politeness, can significantly enhance user satisfaction and interaction quality. However, current conversation design practices often lack clear guidance to support these strategies, leaving designers to rely on personal preferences. To enhance the design of polite chatbots, previous work has investigated the use of politeness parameters, which help in understanding how politeness is expressed in chatbot dialogues through language function variety and indirect communication. In this work, our initial focus is on assessing participants’ perceptions when exposed to different uses of these parameters. To achieve this, three fictional scenarios were presented to six participants to assess the combined impact of various politeness parameters. Although participants acknowledged different polite design strategies, discussing the parameters during the interactions proved challenging. To investigate the use of these parameters during the design process, we instantiated them in a card-based tool with four categories. A workshop was conducted for evaluation where seven participants first designed polite dialogues without the cards. Then, the participants were presented with the cards to reflect on whether they could have supported the design process. Some benefits mentioned by participants included supporting tailored dialogues, guiding design decisions, and maintaining a consistent tone. In summary, our contributions involve evaluating the effectiveness of politeness parameters as design tools, introducing a set of four cards to assist in formulating politeness strategies (currently used in educational settings), and exploring user perceptions when presented with these cards.